EP.FRI.623 Outcome of Rectus Sheath Catheters for Post Operative Analgesia in Patients Undergoing Laparotomies and Elective Colorectal Resections. (28th October 2021) - Darwish, Nourelhuda; Dhahri, AdeelAbbas; Anad, Adam; Sanwu, David; Ivanov, Bogdan
Abstract: Aims: Multimodal analgesia combining regional and local analgesia and avoiding opioids are part of most ERAS protocols aiming to achieve good pain relief. We aim to examine the effectiveness of using rectus sheath catheters (RCSs) for pain relief in patients undergoing laparotomy surgery and wither this have affected the postoperative (30-day) outcome and the need of opioids. Methods: This was a retrospective study involving patients who underwent midline laparotomy surgery, including elective colorectal resections in the period between 01/07/2020 and 23/12/2020. Results: A total of 71 patients were included in the study, of which 40(56.33%) had RSCs while 31(43.66%) did not. Morphine was required for 24(60%) of those with RSCs and for 18 patients (58.06%) with no RSCs. PCA was used in 5 (12.5%) of those with RSCs and in 10 (32.25%) of those without RSCs. Of patients requiring non-PCA morphine, mean total morphine doses were 6.4 in patients with RSCs and 4.89 in patients with no RSCs. Of patients with RSCs, (22.5%, 9/40) developed chest infection within 30 days (average onset at day-11) compared to (25.8%, 8/31) of the other group (average onset at day-5). 20% (8/40) of the patients with RSCs had atelectasis postoperatively compared to 29.03% (9/31) of those who did not. The Average postoperative stay was 13.65 days and 21 days for those with and without RSCs, respectively. Conclusions: Using RSCs did not reduce morphine usage, However, it is associated with lower incidence of chest infection and atelectasis in addition to shorter hospital stay.